الإدمان على المخدرات في المجتمع المحلي (العوامل والحلول)-دراسة ميدانية بحي 08 ماي 1945- بالوادي. - ذيب, محمد (University of Eloued جامعة الوادي, 2021)
هدفت هذه الدراسة التعرف على ظاهرة الإدمان على المخدرات من خلال اتجاهات سكان مدينة الوادي حول المخدرات، والكشف عن ملامح الثقافة السائدة في تفسير هذه الظاهرة، والوعي بأبعادها وسط الفئات الاجتماعية، ولقد أجريت الدراسة في حي 8ماي الواقع بالمدينة الوادي وقع اعتمدنا على عينة عشوائية تضم (4) وحدات سكانيةاخترنا(150) مفردة، وقد خلصت نتائج الدراسة إلى أن أكثر فئات المدمنة على المخدرات هم العاطلون عن العمل وهذا راجع إلى ضعف الدخل الأسري، كما أن أكثر الجهات التي يثق فيها المجتمع في الحد من انتشار المخدرات هم رجال الدين ودائرة مكافحة المخدرات ومعلمو المدارس، وأن أكثر الوسائل التي يراها المجتمع فعّالة في الحد من انتشار ظاهرة الإدمان على المخدرات هي تطبيق القانون الصارم بحق بائعي المخدرات ومروجيها. This study aimed to identify the phenomenon of drug addiction through the attitudes of the residents of the valley regarding drugs, to reveal the features of the prevailing culture in explaining this phenomenon, and awareness of its dimensions among social groups, the study was conducted in the May 8 neighborhood in the city of the Valley. We depended on a random sample of (4) population units. We chose (150) individuals. The results of the study showed that most of the drug addicts were the unemployed. The results of the study were based on a random sample This is due to the weakness of the household income, the most trusted bodies in the society to reduce the spread of drugs are The Anti-Narcotics Department and schoolteachers, and that the most effective means of society in reducing the spread of drug addiction is strict law enfo
مقال
Keywords: ادمان؛ استهلاك؛ تعاطي؛ مخدرات؛ مجتمع محلي.